Charge transport across single-molecule junctions: charge reconfiguration and structural dynamics - Secker, Daniel; Weber, Heiko B. (physica status solidi (b), 2007)
The charge transport across single-molecule junctions is often considered as a pure electronic phenomenon. Analysing experiments performed with the mechanically controlled break junction technique, we show that, additionally, both polarization and dynamic motion of the geometric structure of the molecule give important contributions to the charge transport across single-molecule junctions. (c) 2007 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.